2011
DOI: 10.1007/s10658-011-9770-x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis efficiently eliminates viroid infections from grapevines

Abstract: Indirect somatic embryogenesis is effective at eliminating the most important viruses affecting grapevines. Accordingly, this technique was tested as a method for eradicating two widespread viroids, Grapevine yellow speckle viroid 1 (GYSVd-1) and Hop stunt viroid (HSVd), from four grapevine cultivars. Both viroids were detected by RT-PCR in grapevine floral explants used for initiating embryogenic cultures, as well as in undifferentiated cells of embryogenic and non-embryogenic calli from anthers and ovaries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…This period is shorter than others reported for the sanitation of virus-infected grape varieties (Gambino et al, 2006(Gambino et al, , 2009(Gambino et al, , 2011Borroto-FernĂĄndez et al, 2009).…”
Section: Discussionmentioning
confidence: 64%
“…This period is shorter than others reported for the sanitation of virus-infected grape varieties (Gambino et al, 2006(Gambino et al, , 2009(Gambino et al, , 2011Borroto-FernĂĄndez et al, 2009).…”
Section: Discussionmentioning
confidence: 64%
“…The methodologies commonly employed in the sanitation programmes in grapevine, such as in vitro and/or in vivo thermotherapy, meristem culture, chemotherapy and cryotherapy, show differential success depending on the viral species (Maliogka et al ., ). Some viruses, such as Grapevine rupestris stem pitting‐associated virus (GRSPaV), and viroids are particularly recalcitrant to elimination (Gribaudo et al ., ; Gambino et al ., ). Only somatic embryogenesis has proven very effective against a large number of viruses and viroids, although this is not a commonly‐used technique due to the risk of inducing somaclonal variation (Gambino et al ., , ).…”
Section: What Are the Major Viral Diseases Infecting Grapevine And Homentioning
confidence: 97%
“…Finally, since p23 is an RNA-binding protein (32) with nucleolar (and plasmodesmatal) localization (33), which besides acting as an RSS also regulates viral plus-minus-strand accumulation (34) and movement (27), we cannot eliminate the possibility that some of these functions may also influence the observed effect on viroid accumulation. Intriguingly, Gambino et al found that Grapevine yellow speckle viroid 1, another viroid of the same genus, also accumulates in the nucleus and possibly in the nucleolus (35), although the plants in their study were not directly examined for CDVd.…”
mentioning
confidence: 87%